Unraveling connectivity changes due to dopaminergic therapy in chronically treated Parkinson's disease patients - Ballarini, Tommaso; Růžička, Filip; Bezdicek, Ondrej; Růžička, Evžen; Roth, Jan; Villringer, Arno; Vymazal, Josef; Mueller, Karsten; Schroeter, Matthias L; Jech, Robert (Scientific reports, 2018)
The effects of dopaminergic therapy for Parkinson's disease (PD) on the brain functional architecture are still unclear. We investigated this topic in 31 PD patients (disease duration: 11.2 ± (SD) 3.6 years) who underwent clinical and MRI assessments under chronic dopaminergic treatment (duration: 8.3 ± (SD) 4.4 years) and after its withdrawal. Thirty healthy controls were also included. Functional and morphological changes were studied, respectively, with eigenvector centrality mapping and seed-based connectivity, and voxel-based morphometry. Patients off medication, compared to controls, showed increased connectivity in cortical sensorimotor areas extending to the cerebello-thalamo-cortical pathway and parietal and frontal brain structures. Dopaminergic therapy normalized this increased connectivity. Notably, patients showed decreased interconnectedness in the medicated compared to the unmedicated condition, encompassing putamen, precuneus, supplementary motor and sensorimotor areas bilaterally. Similarly, lower connectivity was found comparing medicated patients to controls, overlapping with the within-group comparison in the putamen. Seed-based analyses revealed that dopaminergic therapy reduced connectivity in motor and default mode networks. Lower connectivity in the putamen correlated with longer disease duration, medication dose, and motor symptom improvement. Notably, atrophy and connectivity changes were topographically dissociated. After chronic treatment, dopaminergic therapy decreases connectivity of key motor and default mode network structures that are abnormally elevated in PD off condition.
Keywords: agonisté dopaminu; Dopamine; mužské pohlaví; Parkinsonova nemoc; Male; Female; Humans; Image Processing, Computer-Assisted; počítačové zpracování obrazu; magnetická rezonanční tomografie; lidé; Time Factors; Middle Aged; ženské pohlaví; lidé středního věku; vztah mezi dávkou a účinkem léčiva; studie případů a kontrol; Case-Control Studies; Nerve Net; Dose-Response Relationship, Drug; Levodopa; Magnetic Resonance Imaging; Parkinson Disease; levodopa; dopamin; nervová síť; časové faktory; Dopamine Agonists